Dietary diversity and depression: cross-sectional and longitudinal analyses in Spanish adult population with metabolic syndrome. Findings from PREDIMED-Plus trial - Naomi Cano-Ibáñez; Lluis Serra-Majem; Sandra Martín-Peláez; Miguel Ángel Martínez-González; Jordi Salas-Salvadó; Dolores Corella; Camille Lassale; Jose Alfredo Martínez; Ángel M Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; et al. (Cambridge University Press, 2023)
Abstract Objective: To examine the cross-sectional and longitudinal (2-year follow-up) associations between dietary diversity (DD) and depressive symptoms. Design: An energy-adjusted dietary diversity score (DDS) was assessed using a validated FFQ and was categorised into quartiles (Q). The variety in each food group was classified into four categories of diversity (C). Depressive symptoms were assessed with Beck Depression Inventory-II (Beck II) questionnaire and depression cases defined as physician-diagnosed or Beck II >= 18. Linear and logistic regression models were used. Setting: Spanish older adults with metabolic syndrome (MetS). Participants: A total of 6625 adults aged 55-75 years from the PREDIMED-Plus study with overweight or obesity and MetS. Results: Total DDS was inversely and statistically significantly associated with depression in the cross-sectional analysis conducted; OR Q4 v. Q1 = 0·76 (95 % CI (0·64, 0·90)). This was driven by high diversity compared to low diversity (C3 v. C1) of vegetables (OR = 0·75, 95 % CI (0·57, 0·93)), cereals (OR = 0·72 (95 % CI (0·56, 0·94)) and proteins (OR = 0·27, 95 % CI (0·11, 0·62)). In the longitudinal analysis, there was no significant association between the baseline DDS and changes in depressive symptoms after 2 years of follow-up, except for DD in vegetables C4 v. C1 = (β = 0·70, 95 % CI (0·05, 1·35)). Conclusions: According to our results, DD is inversely associated with depressive symptoms, but eating more diverse does not seem to reduce the risk of future depression. Additional longitudinal studies (with longer follow-up) are needed to confirm these findings.